Evaluation of the Somatotype of Patients with Class 1, 2 and 3 Obesity According to the Heath-Carter Scheme Using Various Formulas - Muradin M. Semenov; Kseniya V. Vybornaya; Radzhabkadi M. Radzhabkadiev; Kamilat M. Gapparova; Khaider' K. Sharafetdinov; Zainudin M. Zainudinov; Dmitriy B. Nikityuk (Ministry of Health of the Russian Federation. National Medical Research Center of Rehabilitation and Balneology, 2022)
AIM. The purpose of this work was to study the somatotypological characteristics of patients with non-communicable diseases and obesity of class 1, 2 and 3; compare three methods to evaluate the somatotype using three types of complex formulas according to the Heath-Carter scheme; to check the reliability and informativeness of the method of bioimpedance evaluation of somatotype components by regression formulas used in bioimpedance analysis. MATERIAL AND METHODS. 145 patients (67 men, mean age 41.4±10.3 years and 78 women, mean age 40.6±9.4 years) with class 1, class 2 and class 3 obesity, were examined at the clinic of the Federal Research Center of Nutrition and Biotechnology. Anthropometric measurements were taken. Bioimpedance evaluation of body composition was performed using the analyzer ABC-01 "Medas". The somatotype was determined according to the Heath-Carter scheme using three types of complex formulas - based on anthropometry and based on a bioimpedance study of body composition. RESULTS AND DISCUSSION. Based on anthropometric and bioimpedance studies, a characterization of somatotypes according to the Heath-Carter scheme in patients with alimentary-dependent pathologies and class 1, class 2 and class 3 obesity is presented. Significant differences were shown in the values of the somatotype components ENDO and MESO, obtained by calculation using the formulas implemented in the software of the bioimpedance analyzer, from the values obtained by calculating by formulas based on anthropometry. CONCLUSION. The degree of gender dimorphism was different when determining the somatotype according to the Heath-Carter scheme in patients with class 1, class 2 and class 3 obesity, and it depended on what particular formulas were used to calculate the scores. Pronounced gender dimorphism was noted when using both versions of the regression formulas, because they take into account the gender of the individual being examined. It was shown that these formulas are not applicable for evaluation of the components of the somatotype in persons with obesity of class 1, class 2 and class, because the coefficients of determination do not correspond to those previously obtained for a group of people with normal BMI values. We consider it expedient to develop new regression equations for evaluation of the somatotype of the above category of patients.